Análisis de errores de e/le referentes a las partículas, pronombres y adverbios en las producciones de alumnos italianos - Krekovics, Diana (Acta Hispanica, 2008)
The paper proposes to present and analyze the error patterns of Italian native speaker university students with an average level of Spanish in relation with definite and indefinite articles, personal, possessive and demonstrative pronouns, prepositions and adverbs in Spanish. After presenting the principal characteristics of contrastive analysis and error analysis, the author focuses on the analysis of the error patterns. The basis for this is provided by a grammar test prepared by the author, relying on related academic work and personal experience. Apart from this, the paper also relies on data compiled from free compositions prepared by the students. The author provides an analysis and classification of the grammatical errors committed in the tests and compositions, and, after a brief summary of the relevant grammatical rules in Italian, elaborates on the possible causes of the errors.